2020
DOI: 10.1094/pbiomes-01-20-0006-r
|View full text |Cite
|
Sign up to set email alerts
|

Topography-Driven Shape, Spread, and Retention of Leaf Surface Water Impacts Microbial Dispersion and Activity in the Phyllosphere

Abstract: To study the impact of lateral variation in surface topography on the microbial colonization of plant leaves, we used a two-step casting process to generate topomimetic “replicasts” in polydimethylsiloxane which faithfully resembled leaf surface topography at submicrometer scale. This process revealed that the shape and size of the phyllotelma—the collective body of standing water on a leaf surface—was a function of wetting method and presence of surface features, in particular leaf veins. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…Using such PDMS leaf replicasts (i.e., reproductions of plant leaf topography in polydimethylsiloxane), Zhang et al (2014) demonstrated that attachment of E. coli cells to grooves between epidermal cells, replicated from PDMS onto agar, better protected the bacteria from biocide treatment than cells growing on flat agar surfaces. In our own work (Doan et al, 2020) we showed that leaf surfaces with greater topography, i.e., more venation, retained more E. coli cells than flatter surfaces after brief immersion in a bacterial suspension. Similarly, Sun et al (2019) demonstrated that retention of spherical colloids on PDMS replicasts of lettuce, spinach, and tomato fruit was dependent on water retention, which was governed by surface roughness and hydrophobicity of the PDMS replica.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Using such PDMS leaf replicasts (i.e., reproductions of plant leaf topography in polydimethylsiloxane), Zhang et al (2014) demonstrated that attachment of E. coli cells to grooves between epidermal cells, replicated from PDMS onto agar, better protected the bacteria from biocide treatment than cells growing on flat agar surfaces. In our own work (Doan et al, 2020) we showed that leaf surfaces with greater topography, i.e., more venation, retained more E. coli cells than flatter surfaces after brief immersion in a bacterial suspension. Similarly, Sun et al (2019) demonstrated that retention of spherical colloids on PDMS replicasts of lettuce, spinach, and tomato fruit was dependent on water retention, which was governed by surface roughness and hydrophobicity of the PDMS replica.…”
Section: Introductionmentioning
confidence: 84%
“…As a source of leaves for the fabrication of PDMS replicasts, we grew Spinacia oleracea L. (spinach, variety "Tyee, " up to 75 days) from seed in Sunshine mix #1 (Sun Gro Horticulture, Bellevue, WA, United States) in the greenhouse with 10 h of supplemented light (provided by high-pressure sodium light bulbs), and at temperatures ranging from 27 to 30 • C during the day and 18-21 • C at night. Using fresh leaves from 15-, 45-, or 75-days-old spinach plants as templates (leaf ages correspond roughly to those of baby spinach, mature spinach, and freezer spinach, see Koike et al, 2011) PDMS leaf replicasts were prepared in a two-step molding process as described in detail previously (Doan et al, 2020). More specifically, the adaxial (top) and abaxial (bottom) sides of a fresh leaf were used to make a negative mold, and each one of those negatives was used to prepare four identical positive PDMS leaf replicasts.…”
Section: Fabrication Of Pdms Replicastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second and third leaves were taken to mould the leaf surface replica. The process of making artificial leaves was undertaken as previously described [35] and summarized as follows: first, a negative stamp of the adaxial part of the leaf was created. The negative stamp was made with a mixture of 10:1 polydimethylsiloxane (PDMS) and curing agent from a Sylgard 184 PDMS elastomer kit (Dow Chemical, Midland, USA).…”
Section: Construction Of Artificial Leaf Surfaces Bacterial Inoculatmentioning
confidence: 99%
“…The fabricated artificial leaves were autoclaved and rinsed with a mixture of 1:1000 Triton X-100 in distilled water. Artificial leaves were cut into coupons measuring 25.75 cm in diameter and inoculated with 20-µl drops (5 drops per coupon) of a 10 8 CFU/ml bacterial suspension in distilled water [35,36] or in distilled water supplemented with 0.5% quinate, 0.1% galactarate and 0.1% saccharate or with 1 mM isovitexin to mimic endive and melon leaf metabolite profiles, respectively (obtained from the metabolomic analysis). Inoculated coupons were incubated over moistened filter paper with 10 ml of distilled water into a Petri dish plate or without humidity conditions (without distilled water), allowing the drops to dry on an open Petri dish.…”
Section: Construction Of Artificial Leaf Surfaces Bacterial Inoculatmentioning
confidence: 99%